Bulk‐up synchronization of successive larval cohorts of Anopheles gambiae and Anopheles coluzzii through temperature reduction at early larval stages: efect on emergence rate, body size and mating success - Zubair, Q.; Matthews, H.; Sougoufara, S.; Mujeeb, F.; Ashall, S.; Aboagye‑Antwi, F.; Tripet, F. (Malaria Journal, 2021)
Background: Malaria persists as a huge medical and economic burden. Although the number of cases and death rates have reduced in recent years, novel interventions are a necessity if such gains are to be maintained. Alterna‑ tive methods to target mosquito vector populations that involve the release of large numbers genetically modifed mosquitoes are in development. However, their successful introduction will require innovative strategies to bulk-up mosquito numbers and improve mass rearing protocols for Anopheles mosquitoes. Methods: The relationship between mosquito aquatic stage development and temperature was exploited so that multiple cohorts of mosquitoes, from separate egg batches, could be synchronized to ‘bulk-up’ the number of mos‑ quitoes released. First instar larvae were separated into two cohorts: the frst, maintained under standard insectary conditions at 27o C, the second subjected to an initial 5-day cooling period at 19o C. Results: Cooling of 1st instars slowed the mean emergence times of Anopheles coluzzii and Anopheles gambiae by 2.4 and 3.5 days, respectively, compared to their 27o C counterparts. Pupation and emergence rates were good (>85%) in all conditions. Temperature adjustment had no effect on mosquito sex ratio and adult fitness parameters such as body size and mating success. Conclusions: Bulk-up larval synchronization is a simple method allowing more operational fexibility in mosquito production towards mark-release-recapture studies and mass release interventions
Keywords: Anopheles gambiae; Anopheles coluzzii; Larvae development; Mass rearing; Mosquito release programmes; Mark release recapture studies